2016
DOI: 10.1177/1060028016672035
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Low-Dose Methotrexate and Nonsteroidal Anti-inflammatory Drugs, Penicillins, and Proton Pump Inhibitors

Abstract: Given the available evidence, the clinical importance of the interaction between LD-MTX and NSAIDs, penicillins, and PPIs cannot be substantiated. Health care providers should assess the benefit and risk of LD-MTX regardless of concomitant drug use, including factors known to predispose patients to MTX toxicity, and continue to monitor clinical and laboratory parameters per guideline recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 103 publications
0
25
0
9
Order By: Relevance
“…17 Results on pharmacokinetic parameters are conflicting. While concomitant use of NSAIDs did not significantly alter the pharmacokinetic profile of low-dose methotrexate in most studies, 14,17 individual studies have reported important pharmacokinetic changes, including decreased renal clearance of methotrexate with use of ibuprofen and etoricoxib. [28][29][30] Although inconsistent, these data may provide potential mechanistic support for the associations observed in this study.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…17 Results on pharmacokinetic parameters are conflicting. While concomitant use of NSAIDs did not significantly alter the pharmacokinetic profile of low-dose methotrexate in most studies, 14,17 individual studies have reported important pharmacokinetic changes, including decreased renal clearance of methotrexate with use of ibuprofen and etoricoxib. [28][29][30] Although inconsistent, these data may provide potential mechanistic support for the associations observed in this study.…”
Section: Discussionmentioning
confidence: 86%
“…There are no previous controlled studies of concomitant use of methotrexate and NSAIDs that have investigated adverse effects measured as hard clinical endpoints. Previous studies have been small scale and aimed primarily at assessing the pharmacokinetics of methotrexate . A small number of studies have also reported clinical toxicities or adverse effects; however, limitations in sample size and lack of proper control groups render these data largely inconclusive with respect to clinical outcomes .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations